Polarization and frequency-selective properties of a double screen of finite thickness with coaxial-sector aperture - Antonenko, J. V.; Gribovsky, A. V. (Видавничий дім «Академперіодика», 2013)
The polarization and frequency-selective properties of a double screen of finite thickness with coaxial-sector apertures are investigated. The dependences of the reflection coefficient on frequency and distance between the screens are calculated. The Stokes parameters of the reflected wave are analyzed in dependence on distance between the screens for the case of normal incidence of a plane linearly polarized electromagnetic wave upon the structure. It is shown that the reflection coefficient does not depend on polarization angle of the incident wave under certain geometric parameters of the structure.